EPISTEMOLOGI KONTEKSTUAL DAN TEKSTUAL: TAFSIR WAHBAH AL- ZUHAILI DAN SAYYID QUTB TERHADAP AL-MAIDAH 44, 45, 47 - Muhamad Hamdan Tauviqillaah; Edi Komarudin; Wildan Taufik (CV. Adiba Aisha Amira, 2025)
This article aims to study, identify, and compare the epistemology of contextual and textual interpretation of Wahbah Al-Zuhaili and Sayyid in interpreting Surah Al-Ma>’idah verses 44, 45, and 47. This research is qualitative with a comparative analysis method based on library research. The results of this study indicate that Al-Zuhaili interpreted the verses contextually without absolutely justifying infidels by applying specific khita>b targets and detailing the context of the infidel status, so that his views are flexible by prioritizing the realization of maqa>sid al-shari>’ah. Al-Zuhaili's interpretation is based on sources and methods of interpretation that integrate al- ma’thur>r and al-ma’qu>l guided by the analysis of narrations, opinions of companions, and tabi’in, aspects of Islamic knowledge, and opinions of scholars and interpreters. Meanwhile, Sayyid Qutb's interpretation is textual by universalizing the status of kafir for anyone who does not rule by Allah's law, anytime and anywhere. Qutb's interpretation is based on the integration of history and reason with an emphasis on the goals of ideology within the framework of al-tasawwur al-islam>mi> with an approach to analysis of history, muna>sabah, and reflection on reality. The similarity between the two is that both uphold the authority of history and believe that Allah is the main source of law in all aspects of life and those who deny Him doctrinally (belief) are included as kafir.